Comprehensive medication history - Režonja, Renata (Zdravstveno varstvo, 2010)
Introduction: Providing comprehensive medication history (CMH) upon hospital admission is of outmost importance for proper patient evaluation and prescription of drug treatment. The aim of this study was to evaluate the implementation of medication reconciliation in clinical practice. Methods: Patients admitted to a teaching hospital in Slovenia were randomly selected and included in the study. For each patient a CMH was obtained by a research pharmacist using various sources of information. Next, the medication history in the hospital medical record was reviewed. The prescribed drugs were assessed for completeness of information, and possible discrepancies between both medication histories were recorded and classified. Results: Overall, 108 patients with a median age of 73 years were included in the study. The research pharmacist recorded the use of 651 medicaments, with all relevant details being available for 94.9% of these drugs. Of the 464 medicines listed in the hospital medical record, only 42.0% were considered complete. A comparison of the medication history and the medical record with the CMH revealed at least one discrepancy in 72.4% of the drugs listed. The majority of the identified discrepancies were often present both in the medication order on the drug chart (76.2%) and in the discharge letter (69.9%). Most medication discrepancies were due to drug omissions (20.9%) and commissions (6.5%). Conclusion: The high rate of discrepancies between the recorded drug history and CMH reported in our study stresses the need for the implementationof medication reconciliation. The participation of pharmacists in the reconciliation process, described in this study, resulted in more complete and accurate drug histories acquired.
Keywords: Bolnik, sprejem v bolnišnico; bolnišnično zdravljenje; Data Collection; drug; Drug Therapy, Combination; Farmacevtska služba bolnišnice; Hospitalizacija; Hospitalization; informacije; Medical Records; Medicinske kartoteke; Patient Admission; Pharmacy Service, Hospital; Podatki, zbiranje; Prescriptions, Drug; Recepti za zdravila; therapy; zdravila; Zdravilo, terapija sestavljena; zdravljenje